Optimalisasi Pendidikan Inklusi di Indonesia : Tantangan, Permasalahan, dan Strategi Peningkatan Mutu - Anella Roveriana Sitanggang; Anggia Puteri; Elrita Br. Nduru; Erra Fazira MT; Fuza Anggriana; Intan Br. Nainggolan; Meitya Rachdaika Siregar; Lili Tanslionva; Windi Dwi Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Inclusive education in Indonesia faces various challenges, including limited teacher competency, minimal facilities and infrastructure, and low community support for Children with Special Needs (ABK). In addition, obstacles such as negative stigma, lack of training for educators, and policies that are not yet optimal also hamper its implementation. To overcome this, training and improving the quality of teachers, provision of adequate facilities, changes in community paradigms through socialization, and collaboration between schools, government, and the community are needed. Inclusive education can only be successful if it is supported comprehensively by all parties, with a strategic and sustainable approach.